Genetic evidence for efficacy of targeting IL 2, IL 6 and TYK2 signalling in the prevention of type 1 diabetes: a Mendelian randomisation study - Kaiser, Emilia (My University, 2026)
Aims/hypothesis We aimed to investigate the genetic evidence that supports the repurposing of drugs already licensed or in clinical phases of development for prevention of type 1 diabetes. Methods We obtained genome-wide association study summary statistics for the risk of type 1 diabetes, whole-blood gene expression and serum protein levels and investigated genetic polymorphisms near seven potential drug target genes. We used co-localisation to examine whether the same genetic variants that are associated with type 1 diabetes risk were also associated with the relevant drug target genetic proxies and used Mendelian randomisation to evaluate the direction and magnitude of the associations. Furthermore, we performed Mendelian randomisation analysis restricted to functional variants within the drug target genes. Results Co-localisation revealed that the blood expression levels of IL2RA (encoding IL-2 receptor subunit α [IL2RA]), IL6R (encoding IL-6 receptor [IL6R]) and IL6ST (encoding IL-6 cytokine family signal transducer [IL6ST]) shared the same causal variant with type 1 diabetes liability near the corresponding genes (posterior probabilities 100%, 96.5% and 97.0%, respectively). The OR (95% CI) of type 1 diabetes per 1-SD increase in the genetically proxied gene expression of IL2RA, IL6R and IL6ST were 0.22 (0.17, 0.27), 1.98 (1.48, 2.65) and 1.90 (1.45, 2.48), respectively. Using missense variants, genetically proxied TYK2 (encoding tyrosine kinase 2) expression levels were associated with type 1 diabetes risk (OR 0.61 [95% CI 0.54, 0.69]). Conclusions/interpretation Our findings support the targeting of IL-2, IL-6 and TYK2 signalling in prevention of type 1 diabetes.

Tavoitteet Tutkimuksen tarkoituksena oli selvittää, tukeeko geneettinen näyttö IL-2-, IL-6- ja TYK2 signaalireittien kohdentamisen tehokkuutta tyypin 1 diabeteksen ehkäisyssä. Menetelmät Tutkimuksessa hyödynnettiin laajoja genominlaajuisia assosiaatiotutkimuksia (GWAS), ko lokalisaatiota ja Mendelististä satunnaistamista arvioimaan geenien ilmentymisen vaikutusta tyypin 1 diabeteksen riskiin. Ko-lokalisaatiota käytettiin arvioimaan, vaikuttavatko samat geneettiset variantit diabeteksen riskiin ja kohdegeenien ilmentymisen. Mendelistisen satunnaistamisen avulla mitattiin kohdegeenin ilmentymisen vaikutusta tyypin 1 diabeteksen riskiin. Yksi ala-analyysi rajattiin myös geenivariantteihin, jotka muuttivat kohdegeenin koodaamaa proteiinia. Tulokset Ko-lokalisaatio osoitti, että IL2RA-, IL6R- ja IL6ST-geenien ilmentymiseen vaikuttavat geneettiset variantit lisäävät myös tyypin 1 diabeteksen riskiä. Mendelistisen satunnaistamisen perusteella IL2RA:n ilmentymisen lisääntyminen liittyi alhaisempaan diabeteksen riskiin, kun taas IL6R:n ja IL6ST:n ilmentymisen lisääntyminen lisäsi riskiä. Lisäksi TYK2-geenin funktionaaliset variantit osoittivat, että sen ilmentymätason väheneminen liittyy alhaisempaan riskiin sairastua tyypin 1 diabetekseen. Johtopäätökset ja tulkinta Tulokset tukevat näiden signaalireittien kohdentamisen potentiaalia tyypin 1 diabeteksen ehkäisyssä. Erityisesti IL-2:n modulointi ja IL-6:n sekä TYK2:n ilmentymistason säätely näyttäisivät olevan lupaavia strategioita, jotka voivat ohjata tulevia kliinisiä tutkimuksia ja ennaltaehkäisevien hoitomuotojen kehittämistä.
Keywords: IL-2, IL-6, ko-lokalisaatio, mendelistinen satunnaistaminen, TYK2, tyypin 1 diabetes